Inadecuada función motriz y su incidencia en artrosis de mano, personas de 40 a 60 años sector san vicente cantón ventanas los ríos primer semestre 2015 - Ledesma Félix, Solange Annabell (2015)
Osteoarthritis is one of the major rheumatic diseases affect people over 40 years, which generates the wear of the cartilage of the joints to cause intense pain to temporary incapacity as also the deformation of fingers This research paper analyzes San Vicente inadequate motor function and its impact on osteoarthritis of the hand in people aged 40 to 60 of sector San Vicente canton Ventanas Los Ríos, where it was investigated the reasons why this sector suffer from this disease and determent the situation Act in which the inhabitants of the sector they are in study, January to June 2015.